Necip Fazıl’ın Aynadaki Yalan’ Romanında Din ve Tasavvuf / Religious and Mystic Elements in The Novel Aynadaki Yalan (The Lie in the Mirror) - Noyan, Sema (Journal of History Culture and Art Research, 2013)
Öz Yazarın ilk romanı olan Aynadaki Yalan, Batı, Batılılaşma, din ve tasavvuf hakkında yoğun fikirlerin yer aldığı bir eserdir. Batı ve Batılılaşma ile ilgili zengin örneklerin yer aldığı romanda tasavvuf yoluna giren bir akademisyenin macerası anlatılır ve bu vesileyle tasavvuf ve şeriat konusu işlenir. Yazar, romanın başkahramanı Naci aracılığıyla insanlığın kurtuluşu için tek modelin İslam olduğu vurgusu yapar. Yazarın, bu romanında din ve tasavvuf hakkında ele aldığı fikirlerini başka yazılarında ve eserlerinde de görmek mümkündür. İdeologya Örgüsü ve Batı Tefekkürü ve İslam Tasavvufu adlı çalışmaları buna örnek gösterilebilir. Aynadaki Yalan, bu fikirlerin bir derlemesi ve kurgu içinde sunulmasından ibarettir. Bir entelektüelin özüne dönüşünü konu edinen bu romanda ele alınan din ve tasavvuf kavramları araştırmada ayrıntılı bir şekilde incelenmiştir. Abstract The author’s first novel Aynadaki Yalan (The Lie in the Mirror) is a work which analyzes a westernized Turkish intellectual. The work which involves rich ideas about West, being Westernized, religion, and mysticism, narrates the adventure of an intellectual turning back his own morals. By virtue of the protagonist, Naci, author gives the message that the only model and the order for mankind is Islam. It is possible to see the author’s ideas about religion and mysticism, in his other essays and works. The novel goes parallel with the author Necip Fazıl’s other works like İdeologya Örgüsü (Ideology Plot) and Batı Tefekkürü ve İslam Tasavvufu (Western Contemplation and Islamic Mysticism). Aynadaki Yalan (The Lie in the Mirror) consists of presenting an edited version and a compilation of the ideas in these works. It is determined that the studies made on the novel Aynadaki Yalan (The Lie in the Mirror) does not gives detailed information in this aspect of the work, so in this study the importance of returning to self and tradition of a Turkish intellectual is emphasized laying stress on the concept of religion and mysticism.